PRACTICAL METHODS AND REAL CHALLENGES IN TEACHING ENGLISH (Лучшие интеллектуальные исследования, 2025)
Abstract Teaching English at the university level requires a structured approach that balances theoretical knowledge with practical application. This study examines the most effective methodologies, challenges, and innovations in university-level English language teaching. The research highlights traditional and modern teaching techniques, focusing on academic writing, critical thinking, and digital learning tools. The findings suggest that a combination of communicative, task-based, and technology-assisted approaches leads to the most successful language acquisition at the higher education level.